Evaluating student acceptance of interactive infographics module for Arabic grammar learning using the Technology Acceptance Model (TAM) - Abdul Hamid, Mohd Fauzi; Sahrir, Muhammad Sabri; Amiruddin, Ahmad Zaki; Yahaya, Mohd Firdaus; Sha’ari, Shaferul Hafes (Society for Research and Knowledge Management Ltd, Mauritius, 2024)
Arabic grammar learning textbooks are often associated with lengthy and unfocused information. Text-only content contributes to students’ disinterest in learning and in-depth comprehension of a subject. Infographics have emerged as a substitute for traditional textbooks offering a more engaging and straightforward way to deliver knowledge through basic technological applications. An interactive infographic module based on a website has been developed and practiced for students as an alternative to the problem. This study aims to identify the level of student acceptance of the interactive infographic modules based on the Technology Acceptance Model (TAM) and identify attitudes toward usage, readiness and behavioral intention for usage. A total of 72 students of Bachelor in Arabic Studies at Universiti Sultan Zainal Abidin, Malaysia were involved as survey respondents. To gather information, a set of questionnaires was distributed and an infographic website module was developed. The quantitative study’s data was descriptively analyzed using SPSS to assess how students accepted technology in terms of their attitude towards usage, readiness and behavioral intention for the module, and perceptions of its practicality and simplicity of use. The findings indicate that students who use technology have a high level of acceptability for the technology module and are prepared to continue learning Arabic grammar through the designed module because they see its advantages. The high ratings for these items indicate that the module improved their understanding of the material. The students’ interaction with the module was clear and easy to understand. They believe that a website-based interactive infographic module is an effective tool for learning Arabic grammar. This module is designed to supplement classroom textbook instruction. This study is considered a contribution to the use of technology in learning courses with extensive syllabuses that require conveniently available and better-understood supplementary materials.